The power of the prosecution to modify the criminal charges and its implications for the defendant’s position - Briški, Lora (Glasnik Advokatske komore Vojvodine, 2024)
Evidence presented during the trial may portray the criminal offence differently than described in the indictment. The same set of facts may require a different legal qualification or newly discovered facts may show that the prosecutor’s initial description of events should be different. Two potential solutions to this problem exist: the prosecution loses the case or is allowed to modify the charges. In Slovenian criminal procedure, the prosecutor is granted the authority to modify the charge during the trial. This paper focuses on the question of how broad are the powers of the Slovenian prosecutor to modify the criminal charge and how the existence of this power, along with its scope, affects the position of the defence. For that reason, we have examined the decisions of the Slovenian Constitutional Court and ordinary courts. After establishing the extent to which modifications can occur in practice, we highlight potential critical points associated with the modification of the charge, as provided for in the current regulation. Finally, we consider reform options that would improve the defendant’s position.